Ablation of Central Serotonergic Neurons Decreased REM Sleep and Attenuated Arousal Response - Iwasaki, Kanako; Komiya, Haruna; Kakizaki, Miyo; Miyoshi, Chika; Abe, Manabu; Sakimura, Kenji; Funato, Hiromasa; Yanagisawa, Masashi (Frontiers in Neuroscience, 2018)
Sleep/wake behavior is regulated by distinct groups of neurons, such as dopaminergic, noradrenergic and orexinergic neurons. Although monoaminergic neurons are usually considered to be wake-promoting, the role of serotonergic neurons in sleep/wake behavior remains inconclusive because of the effect of serotonin (5-HT)-deficiency on brain development and the compensation for inborn 5-HT deficiency by other sleep/wake-regulating neurons. Here, we performed selective ablation of central 5-HT neurons in the newly developed Rosa-diphtheria toxin receptor (DTR)-tdTomato mouse line that was crossed with Pet1Cre/+ mice to examine the role of 5-HT neurons in the sleep/wake behavior of adult mice. Intracerebroventricular administration of diphtheria toxin completely ablated tdTomato-positive cells in Pet1Cre/+; Rosa-DTR-tdTomato mice. Electroencephalogram/electromyogram-based sleep/wake analysis demonstrated that central 5-HT neuron ablation in adult mice decreased the time spent in rapid eye movement (REM) sleep, which was associated with fewer transitions from non-REM (NREM) sleep to REM sleep than in control mice. Central 5-HT neuron-ablated mice showed attenuated wake response to a novel environment and increased theta power during wakefulness compared to control mice. The current findings indicated that adult 5-HT neurons work to support wakefulness and increase REM sleep time through a biased transition from NREM sleep to REM sleep.